Jurnal Surya Masyarakat - Universitas Muhammadiyah Semarang. Lembaga Penelitian dan Pengabdian Masyarakat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Semarang, 2018)
Journal focuses on problems dealing with the community services.
Keywords: Community development : Indonesia : Periodicals